The effectiveness of biomechanical technology-based sports training models in improving elementary school students' motor skills - Timba, Frederiksen Novenrius Sini; Chandra, Conchita Junita; Rawe, Aschari Senjahari; Mbari, Maria Angelina Fransiska (Indonesian Journal of Educational Development (IJED), 2025)
Fundamental motor skills are an essential foundation for the holistic development of elementary school students, influencing their health, self-confidence, and academic success. This study aims to develop and test the effectiveness of a Biomechanics-Integrated Technology-Based Sports Training Model (VAB-F) to improve elementary school students' long jump motor skills. This study employed a multidisciplinary design, utilising mixed methods and a sequential explanatory approach, with a quantitative stage in the form of a quasi-experiment (pre-test post-test control group design) involving 60 fifth-grade students from SDK Magepanda. The sample was randomly divided into an experimental group (n = 30) and a control group (n = 30). Motor skills were assessed using a validated long jump technique quality assessment rubric, which was supplemented with biomechanical analysis through the Kinovea application and a Wearable Activity Tracker. The qualitative stage consisted of interviews with 6 students and 2 teachers. The results showed that the experimental group experienced a statistically significant increase in skill scores (an average increase of 29.70 points) compared to the control group (an average increase of 9.60 points), with the t-test results indicating a highly significant difference (t(58) = 15.23, p < 0.05). The qualitative results showed that the visual feedback technology encouraged independence, motivation, and intuition of student movement efficiency. It was concluded that the VAB-F training model was significantly more effective than traditional methods in improving the long jump motor skills of elementary school students.